Early farming in the Algarve (Southern Portugal): a preliminary view from two cave excavations near Faro - Straus, L. G.; Altuna, J.; Ford, D.; Marambat, L.; Rhine, J. S.; Schawrcz, J-H. P.; Vernet, J-L. (Trabalhos de Antropologia e Etnologia, 2021)
.